THE ADAPTATION OF THE EASY-CARE STANDARD ASSESSMENT INSTRUMENT INTO TURKISH AND EVALUATION OF PSYCHOMETRIC PROPERTIES AMONG TURKISH OLDER PEOPLE - (:unkn) unknown (NOBEL ILAC, 2015)
Objective: The assessment of older people's needs is an important indicator for planning individual care and services that promote independence, health and well-being. However, there is not a valid tool to measure physical, mental, and social needs of older people in Turkey. The purpose of the study was to adapt of EASY-Care Standard, which is a comprehensive and holistic assessment tool, into Turkish and evaluate its psychometric properties. Material and Method: The sample consisted of 400 older people. The EASY-Care Standard covers seeing, hearing and communicating, looking after yourself, getting around, accommodation and finance, safety and relationships, staying healthy, mental health and wellbeing. Scores representing overall level of independence, risk of breakdown in care and risk of falls are calculated from the selected items' scores. Forward-back translation method was used to adapt EASY-Care into Turkish. Reliability was assessed using internal consistency, item-total correlation and test-retest stability. Construct validity was analyzed by investigating associations between the three sub domains in EASY-Care and testing convergent and divergent validity. Results: We found satisfactory evidence for reliability and construct validity. Kappa statistics were acceptable, Intraclass correlation coefficients (ICC) and Cronbach's alpha values were satisfactory. Convergent validity was supported by moderate to high negative correlations between EASY-Care Standard and the The MOS 36-item short-form health survey (SF-36). The EASY-Care scores were differentiated by living arrangements, educational status, perceived health, urinary incontinence, depression, malnutrition, and history of hospital admission within last three years. Conclusion: In conclusion, the EASY-Care Standard is a reliable and valid instrument for older people in Turkey.
Keywords: Elderly; psychometric properties; reliability; validity; QUALITY-OF-LIFE; URINARY-INCONTINENCE; COMMUNITY; HEALTH; DEPRESSION; FALLS; RISK; HOME; RELIABILITY; ELDERS